Pengaruh Tehnik Relaksasi Autogenik terhadap Kadar Gula Darah pada Penderita Diabetes Mellitus Tipe 2 - Ardiansyah, Fourni; Harison, Nunu; Shinta, Shinta; Amita, Dita; Hayani, Afrida (Universitas Malahayati, 2023)
ABSTRACT Type 2 diabetes mellitus is a chronic disease characterized by hyperglycemia due to the inability to metabolize carbohydrates, fats, proteins. Type 2 diabetes mellitus can be controlled with autogenic relaxation non-pharmacological therapy. To determine the effect of autogenic relaxation techniques on blood sugar levels in patients with type 2 diabetes mellitus. This research is a quasi-experimental research with pre and post test. The research was conducted at the O. Mangunharjo Health Center with a sample of 10 people. Sampling by purposive sampling. Measurement of blood sugar levels was carried out before and after administration of therapy. Autogenic therapy was given 12 times with a duration of 15 minutes. Data analysis was performed by comparing the average blood sugar levels before and after autogenic relaxation with paired t test. The results showed that the average blood sugar level was before 252 mg/dl and after 230 mg/dl. The average age of the respondents was 59 years and the duration of suffering from DM was 7 years. From the results of the paired t test, p = 0.001. The conclusion of the study is that there is an effect of autogenic relaxation techniques on sugar levels in people with type 2 diabetes mellitus at the puskesmas o. mangunharjo, purwodadi district, musi rawas district. Keywords: Autogenic Relaxation Technique, Blood Sugar Levels, Type 2 DM ABSTRAK Diabetes melitus tipe 2 merupakan penyakit kronis ditandai hiperglikemia akibat ketidakmampuan melakukan metabolisme karbohidrat, lemak, protein. Diabetes melitus tipe 2 dapat dikontrol dengan terapi nonfarmakologis relaksasi autogenik. Diketahui pengaruh tehnik relaksasi autogenik terhadap kadar gula pada penderita diabetes mellitus tipe 2. Penelitian ini merupakan penelitian quasi eksperimen dengan pre dan post test. Penelitian dilakukan di puskesmas O. Mangunharjo dengan sampel sebanyak 10 orang. Pengambilan sampel dengan purposive sampling. Pengukuran kadar gula darah dilakukan sebelum dan setelah pemberian terapi. Terapi autogenic diberikan selama 12 kali dengan durasi 15 menit. Analisa data dilakukan dengan membandingkan rata-rata kadar gula darah sebelum dan sesudah relaksasi autogenic dengan Uji paired t test. Hasil penelitian didapatkan rata – rata kadar gula darah sebelum 252 mg/dl dan setelah 230 mg/dl. Rata rata usia responden 59 tahun dan lama menderita penyakit DM 7 tahun. Dari hasil uji paired t test diperoleh p = 0. 001.Kata Kunci : Teknik Relaksasi Autogenik, Kadar Gula Darah, DM Tipe 2